2012
DOI: 10.1002/imhj.20339
|View full text |Cite
|
Sign up to set email alerts
|

Children's emotional responsiveness and sociomoral understanding and associations with mothers' and fathers' socialization practices

Abstract: Sixty-two preschoolers (55% boys) were presented hypothetical dilemmas about moral transgressions. Responses were evaluated in terms of children's emotional responsiveness, prosocial motives, and readiness to intervene. Mothers and fathers reported separately on their use of victim-oriented inductions, teaching reparations, power assertion, and love withdrawal. Four years later, parents reported on children's behavioral problems, emotion-regulation ability, and empathy. Mothers reported using more victim-orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 78 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…In young children, maternal intrusiveness and/or negative affect predicted decreases in toddlers' concern for others over time (J. L. Robinson et al, 1994) and less concern as reported by mothers (but not as observed) among preschoolers (Hastings et al, 2000). At the same time, mothers' love withdrawal, a specific psychological control practice, has been positively linked to toddlers' reparation after causing distress to others (Zahn-Waxler et al, 1979), and to preschoolers' interview responses reflecting concern for others (Garner, 2012), and was unrelated to empathy in a sample of sixth and seventh graders (Krevans & Gibbs, 1996). Another psychologically controlling technique, guilt induction, predicted increases in prosocial behavior 6 months later among Chinese American preschoolers who were less well-regulated, and did not significantly impact better-regulated children (Yu et al, 2018).…”
Section: Religiosity As a Moderator Of The Links Between Parental Psychological Control And Children's Prosocialitymentioning
confidence: 87%
“…In young children, maternal intrusiveness and/or negative affect predicted decreases in toddlers' concern for others over time (J. L. Robinson et al, 1994) and less concern as reported by mothers (but not as observed) among preschoolers (Hastings et al, 2000). At the same time, mothers' love withdrawal, a specific psychological control practice, has been positively linked to toddlers' reparation after causing distress to others (Zahn-Waxler et al, 1979), and to preschoolers' interview responses reflecting concern for others (Garner, 2012), and was unrelated to empathy in a sample of sixth and seventh graders (Krevans & Gibbs, 1996). Another psychologically controlling technique, guilt induction, predicted increases in prosocial behavior 6 months later among Chinese American preschoolers who were less well-regulated, and did not significantly impact better-regulated children (Yu et al, 2018).…”
Section: Religiosity As a Moderator Of The Links Between Parental Psychological Control And Children's Prosocialitymentioning
confidence: 87%
“…Thus, inductions are expected to direct children's attention to outcomes for others and how they can affect others' emotional states and well-being. In fact, consistent with theory, parental inductive discipline (i.e., the use of reasoning) tends to be positively related to prosocial behavior, empathy, and sympathy (Carlo, Knight, McGinley, & Hayes, 2011;Krevans & Gibbs, 1996;Janssens & Gerris, 1992;Laible, Eye, & Carlo, 2008; see Eisenberg et al, 2006), although researchers do not always find significant relations (e.g., Garner, 2012). However, none of the existing work, to our knowledge, has examined these relations from childhood into adulthood.…”
Section: Style Of Parental Disciplinementioning
confidence: 79%
“…Although parents may feel reliant on conventional justification to enforce the rules, it may be useful for parents to discuss with their children other reasons why their misbehavior is undesirable, particularly reasons that appeal to the child’s understanding of morality, relationships with others, or the consideration of others’ feelings. These parenting approaches have been shown to increase prosocial behavior in young children (Garner, 2012).…”
Section: Discussionmentioning
confidence: 99%